Exploring the Science of Society - Arora, Pankaj (JOURNAL OF INDIAN EDUCATION, 2014)
The present article is an attempt to present a sketch of the origin, evolution, present and future of the discipline— Social Science. The author has strongly advocated that the Social Science had never been given its due place/respect in the world of knowledge. Author emphasised that the study of Human Society has always fascinated the intellectuals and theorists, but they hold different views about the nature of this study. Should it be like that of Natural Sciences or it can remain scientific with its own characteristics? Do we need to study human society in a style which is close to the study of natural science or it can have the flexibility to accommodate the dynamic strength of different dimensions of the society, such as pluralism, democracy and liberalism etc. Various debates in this regard from Auguste Compte to David Easton and Carl Popper have been discussed and presented in this write-up. At the end of this article, author has supported the idea of granting it the status of soft science, which, not only, uphold the scientific flavor in the study of social science but also, accommodate the unique characteristics of the discipline of social science. We need to encourage social science research at university level and community level to facilitate the generation of new knowledge in social science and this is the need of the 21st century.